Response of human pulps to different in-office bleaching techniques: preliminary findings - Roderjan, Douglas Augusto; Stanislawczuk, Rodrigo; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Reis, Alessandra; Loguercio, Alessandro D. (Fundação Odontológica de Ribeirão Preto, 2015)
This study evaluated a whitening effect and the likely side effect (tooth sensitivity and pulp response) of human teeth subjected to different in-office bleaching (IOB) techniques and materials, mainly the presence of calcium in the IOB materials. A calcium-free (CF) and a calcium-containing (CC) 35% hydrogen peroxide (HP) gels were evaluated. The CF was refreshed every 15 minutes, three times (CF 3-15) or in a single 45-min application (CF 1-45) at one bleaching appointment. The CC was used only in a single 45-min application (CC 1-45). Each technique was applied in 5 mandibular incisors scheduled for extraction for different patients. In control group, no tooth bleaching was performed. The tooth colour (TC) and tooth sensitivity (TS) were recorded at baseline and after IOB. The teeth were extracted 2 days after the application of IOB and subjected to histological analysis. The data was submitted to appropriate statistical analysis (α=0.05). The changes of TC were similar between groups and statistically different from the control (p<0.05). However, TS of groups bleached with CF was statistically higher than that recorded for CC and the control (p<0.05). In CF 3-15 and CF 1-45 groups, the coronal pulp tissue exhibited partial necrosis associated with tertiary dentin deposition. In CC 1-45 group smaller area of necrosis occurred only in three bleached teeth in which tertiary dentin deposition was observed. The calcium-containing 35%HP gel could be preferable for in-office bleaching because it caused less tooth sensibility and pulp damage.

O objetivo do estudo foi avaliar o efeito clareador e seus efeitos adversos (sensibilidade e resposta pulpar) de dentes humanos submetidos a diferentes técnicas e materiais para o clareamento em consultório (CLCO), principalmente a presença de cálcio nos materiais para CLCO. Um agente clareador a base de peróxido de hidrogênio (PH) a 35% sem cálcio (SC) e com cálcio (CC) foram avaliados. O agente clareador SC foi usado em duas técnicas de aplicação: o gel clareador foi reaplicado a cada 15 minutos, três vezes (SC 3-15) ou 1 x 45-min por aplicação (SC 1-45) em uma sessão clínica. O agente clareador CC foi usado apenas em 1 x 45-min por aplicação (CC 1-45). Cada técnica foi aplicada em 5 incisivos inferiores indicados para extração de pacientes diferentes. No grupo controle, o clareamento não foi realizado. O efeito clareador (EC) e a sensibilidade dental (SD) foram registrados inicialmente e após o CLCO. Os dentes foram extraídos após 2 dias da aplicação do CLCO e foram submetidos ao análise histológica. Os dados foram submetidos a análise estatística apropriada (α=0.05). As mudanças foram semelhantes entre os grupos e significativamente diferentes do controle (p<0.05). Entretanto, a SD nos grupos clareados com SC foi estatisticamente maior do que a registrada nos grupos CC e do grupo controle (p<0.05). Nos grupos SC 3-15 e SC CF 1-45, o tecido pulpar da região coronária exibia necrose parcial associada a deposição de dentina terciária. No grupo CC 1-45, pequenas áreas de necrose ocorreram somente em 3 dentes clareados, nos quais deposição de dentina terciária também foi observada. O gel CC de HP a 35%HP gel poderia ser preferível para a realização de CLCO devido ao fato de causar menos danos ao tecido pulpar
Keywords: Tooth bleaching; Hydrogen peroxide; Materials testing; Metabolism